PENGARUH SIKAP WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN (PBB) DI KECAMATAN MOTOLING DI KABUPATEN MINAHASA SELATAN - Wowor, Vianny M.L.; Sabijono, Harijanto; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Land and Property Tax is a tax system with a semi self assesment where the moreproactive and cooperative do the calculations is revenue officer, the tax payable and distribute assignment to local governments through the regional Revenue Office based on the notice of Tax Objects is filled by the Taxpayer or the verification of revenue officer on field. Consciousness to be a taxpayer who dutifully is one of obedience to the law. Compliance with the payment of taxes including a code of conduct against tax law indiscriminately and did not escape from the exception. This research aims to know attitude of the taxpayer, the influence of the existence of sanctions, fines and influence service of revenue officeragainst taxpayer compliance in payments land and property tax to the districts in Motoling. This research using quantitative research correlation methods. The results showed that the attitude of the taxpayer do not affect positively against taxpayer compliance in payments to the land and property tax . However the existence of sanctions fines and good service from revenue officer give a positive effect against the land and property tax payment compliance in district Motoling. Penalties and good service from revenue officer increase taxpayer compliance in district Motoling in payments to the land and property tax.Key words: attitude of the taxpayers, sanctions, service of revenue officer, taxpayer compliance